LAC Success Put to Test - World Bank (Washington, DC, 2017)
This semiannual report, a product of the Office of the Chief Economist for the Latin America and the Caribbean (LAC) region of the World Bank, examines the nature of the very good overall performance of the LAC region in the aftermath of the 2008-09 global financial crisis and presents a comparative analysis of the post-crisis recovery patterns in the region vis-a-vis other regions. The first part of this report provides an overview of recent economic developments, an in depth look at the drivers of the post-crisis performance in the region, analyzes the external and domestic risks that could drag down growth performance in LAC, and discusses policy response options. The second part of the report documents the adverse impact of the crisis on the Caribbean region as well as its slow recovery. It distinguishes the poorer performance of English speaking Caribbean nations vis-a-vis non-English speaking ones, and highlights the dependence of the region on countries in the epicenter of the crisis, especially the United States, and the limited fiscal space that disabled a counter-cyclical policy response. The report concludes by emphasizing that skillful cycle management is necessary although far from sufficient to be able to turn what has to date been a cyclical recovery into a higher rate of trend growth. Moreover, countries experiencing a formidable windfall from the high commodity prices are in a unique position to seize the opportunity by judiciously saving and investing out of the windfall, they could relax the structural speed limits that have so far kept economic activity from rising to a higher long-run growth path.